Opinion of the Italian Association of Myology on Ataluren for the Treatment of Nonsense Mutation Duchenne Muscular Dystrophy - Luca Bello; Pietro Riguzzi; Emilio Albamonte; Guja Astrea; Roberta Battini; Andrea Barp; Angela L. Berardinelli; Enrico S. Bertini; Noemi Brolatti; Claudio Bruno; Stefania Corti; Adele D’Amico; et al. (Drugs in R&D, 2025)
Abstract The Italian Duchenne muscular dystrophy expert clinicians, gathered in the Italian Association of Myology (AIM), intend to express a position against the suspension of the Marketing Authorization of ataluren (Translarna®) for the treatment of nonsense mutation Duchenne muscular dystrophy. The marketing authorization has been recently withdrawn by the European Commission following a recommendation from the Committee for Medicinal Products for Human Use of the European Medicines Agency. This negative recommendation was based on the fact that three randomized controlled trials of ataluren in nonsense mutation Duchenne muscular dystrophy (007, 020, and 041) have failed to show statistically significant differencs in favor of the treatment in the selected primary outcomes for each individual study, i.e., 6-min walk distance, in the intent-to-treat population for 007 and 020 and in a subgroup for 041. However, observed differences always favored treatment, and several clinically meaningful secondary outcomes were positive and statistically significant across studies. Importantly, the largest and longest phase III study (041) showed a statistically significant effect in favor of ataluren in the wider intent-to-treat population. Furthermore, a long-term registry of “real-world” ataluren treatment data (Strategic Targeting of Registries and Database of Excellence, STRIDE), in addition to confirming a reassuring safety profile, suggested a prolonged maintenance of ambulatory, upper limb, and respiratory function. We deem that a withdrawal of ataluren from the European market would harm not only patients with nonsense mutation Duchenne muscular dystrophy, but the whole neuromuscular field, in which clinical trials are challenging because of the heterogenous complex slow-progressing nature of the disorders.